Biofilm microbial communities of denture stomatitis - Campos, M. S.; Marchini, L. [UNESP]; Bernardes, L. A. S.; Paulino, L. C.; Nobrega, F. G. (Wiley-Blackwell, 2008)
Introduction: Denture stomatitis is a common lesion that affects denture wearers. Its multifactorial etiology seems to depend on a complex and poorly characterized biofilm. The purpose of this study was to assess the composition of the microbial biofilm obtained from complete denture wearers with and without denture stomatitis using culture-independent methods.Methods: Samples were collected from healthy denture wearers and from patients with denture stomatitis. Libraries comprising about 600 cloned 16S ribosomal DNA (rDNA) bacterial sequences and 192 cloned eukaryotic internal transcribed spacer (ITS) region sequences, obtained by polymerase chain reactions, were analyzed.Results: The partial 16S rDNA sequences revealed a total of 82 bacterial species identified in healthy subjects and patients with denture stomatitis. Twenty-seven bacterial species were detected in both biofilms, 29 species were exclusively present in patients with denture stomatitis, and 26 were found only in healthy subjects. Analysis of the ITS region revealed the presence of Candida sp. in both biofilms.Conclusion: The results revealed the extent of the microbial flora, suggesting the existence of distinct biofilms in healthy subjects and in patients with denture stomatitis.
Keywords: denture stomatitis; internal transcribed spacer region; oral biofilms; ribosomal genes